PENEGAKAN HUKUM PIDANA TERHADAP PENCEMARAN LINGKUNGAN DANAU TOBA OLEH MASYARAKAT PENGELOLA KERAMBA JARING APUNG (KJA) - Pardosi, Pretty Elisabeth (Universitas Harapan Medan, 2023)
Lakes have a significant economic function, namely as a source of clean water which is very important for human needs such as providing drinking water, irrigation, and industrial purposes. One of the lakes owned by Indonesia is Lake Toba. The community uses the Lake Toba area for agriculture, tourism, and fisheries. Floating net cage (KJA) is one of the freshwater fish farming systems that developed in the Lake Toba area. The existence of KJA in Lake Toba is able to improve the community's economy resulting in its use increasing from year to year. However, its management has a negative impact on the environment, such as Lake Toba water pollution. This research will examine criminal law enforcement related to the management of Floating Net Cages (KJA) that pollute the environment in Lake Toba and solutions to the problem of managing Floating Net Cages (KJA) that pollute the Lake Toba environment. This research is a normative legal research, which is descriptive (exposure). Normative legal research is a document study, which uses sources of legal material in the form of laws and regulations, court decisions / decrees, contracts / agreements / contracts, legal theories, and opinions of scholars. The results showed that law enforcement of KJA managers who pollute the environment in Lake Toba is still weak, even though there is a legal umbrella that regulates it. Countermeasures can be divided into pre-emptive action, preventive action and repressive action. Pre-emptive action can be done by conducting a Strategic Environmental Assessment (KLHS) program, while preventive action can be done by being selective in granting environmental permits, and repressive action is by imposing strict sanctions in accordance with applicable regulations. Keywords: Criminal Law Enforcement, KJA Management, Environmental Pollution.